The Influence of Whatsapp, Teacher Support and Attitude of Adolescent Girls Towards Compliance In Taking Iron Supplement Tablets: Systematic Review - Rika Viyanti; Siti Aisah; Satriya Pranata (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia is a significant health issue among adolescent girls, often caused by iron deficiency. Compliance in consuming Iron Tablets (Tablet Tambah Darah, TTD) is crucial to address this condition. This study aims to systematically review the influence of WhatsApp, teacher support, and attitudes of adolescent girls on TTD compliance. The method used is a systematic review with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) approach. A search conducted on journals indexed by SINTA and Scopus resulted in a total of 860 journals using the keywords anemia, iron supplement compliance, adolescents, technology WhatsApp, teacher support, and attitudes. Of these, 15 journals met the inclusion criteria and were further analyzed. The results of the study indicate that the use of WhatsApp can enhance awareness and knowledge of adolescent girls about the importance of consuming TTD, although the outcomes vary. Teacher support has also been shown to play an important role in improving compliance, as teachers can provide the necessary encouragement and supervision. Positive attitudes of adolescent girls towards TTD consumption significantly contribute to compliance. In conclusion, the combination of communication technology, teacher support, and fostering positive attitudes can enhance TTD compliance among adolescent girls. This multidimensional approach can be an effective strategy to reduce the prevalence of anemia among adolescent girls.